Market Analysis and Entrepreneurial Development of Dairy Farms in the Agricultural Sector - Mosiiuk, Volodymyr; Misiuk, Mykola; Zakhodym, Maryna; Susharnyk, Yaroslav (Dr. Viktor Koval, 2025)
Introduction. The development of entrepreneurship in the dairy industry can ensure food security, increase budget revenues by increasing the volume of dairy product exports, and create jobs in post-war Ukraine. Since the dairy business involves production, processing, storage, logistics, and sales of dairy products, this opens up vast opportunities for developing diverse entrepreneurial activities involving workers with different qualification levels. Aim and tasks. This study aims to analyse market conditions and substantiate the directions of entrepreneurial development of dairy production entities in Ukraine in the post-war period. It further seeks to forecast the dairy market indicators of Ukraine using the ARMA approach, assess the significance of changes in dairy market indicators in the first post-war years, and substantiate the barriers to entrepreneurial activity of dairy business entities. Results. The adaptive method of step-by-step refinement of the forecast indicator specified a reduction in imports in 2027 compared to 2024 by 10.7%, provided that domestic demand grew by 7.76% and exports increased by 26.3%. The share of cattle in small farms in 2027 will be 3.5% less than that in 2021, and the share of cows will be 1.1% less. A gradual increase improves the prerequisites for entrepreneurial activity in livestock farming and milk production profitability. This is confirmed by forecast data on the growth of average milk yield from 0.85% to 4.2% by farm size for the first post-war years, since the growth of milk yield is one of the factors increasing the profitability of dairy enterprises. Conclusions. With the growing volumes of supplies for processing from large enterprises, there is a tendency to reduce supplies from small farms, which increases the differentiation of dairy farms in terms of the volume of coverage of external and internal markets. When defining promising areas, obstacles to the entrepreneurial activity of dairy business entities were identified. This indicates that the specified activity should be aimed at the glocalisation of production and sales. This will provide an opportunity to use sales in external markets and operational manoeuvring in markets as a tool for regulating production volumes. This indicates that cooperation contributes to solving the problems of providing workers and intensifying the development of human capital in agricultural production, which is currently hindered by a small share (18%) of dairy farms in the cooperation process.